Global consensus statement on simulation-based practice in healthcare - Diaz-Navarro, Cristina; Armstrong, Robert; Charnetski, Matthew; Freeman, Kirsty J; Koh, Sabrina; Reedy, Gabriel; Smitten, Jayne; Ingrassia Luigi, Pier; Matos Maio, Francisco; Issenberg, Barry (Simulation in healthcare : journal of the Society for Medical Simulation, 2024)
Simulation plays a pivotal role in addressing universal healthcare challenges, reducing education inequities, and improving mortality, morbidity and patient experiences. It enhances healthcare processes and systems, contributing significantly to the development of a safety culture within organizations. It has proven to be cost-effective and successful in enhancing team performance, fostering workforce resilience and improving patient outcomes.Through an international collaborative effort, an iterative consultation process was conducted with 50 societies operating across 67 countries within six continents. This process revealed common healthcare challenges and simulation practices worldwide. The intended audience for this statement includes policymakers, healthcare organization leaders, health education institutions, and simulation practitioners. It aims to establish a consensus on the key priorities for the broad adoption of exemplary simulation practice that benefits patients and healthcare workforces globally. Advocating for the benefits that simulation provides to patients, staff and organizations is crucial, as well as promoting its adoption and integration into daily learning and practice throughout the healthcare spectrum. Low-cost, high-impact simulation methods should be leveraged to expand global accessibility and integrate into system improvement processes as well as undergraduate and postgraduate curricula. Support at institutional and governmental level is essential, necessitating a unified and concerted approach in terms of political, strategic and financial commitment.It is imperative that simulation is used appropriately, employing evidence-based quality assurance approaches that adhere to recognized standards of best practice. These standards include faculty development, evaluation, accrediting, credentialing, and certification.We must endeavor to provide equitable and sustainable access to high-quality, contextually relevant simulation-based learning opportunities, firmly upholding the principles of equity, diversity and inclusion. This should be complemented with a renewed emphasis on research and scholarship in this field. We urge policymakers and leaders to formally acknowledge and embrace the benefits of simulation in healthcare practice and education. This includes a commitment to sustained support and a mandate for the application of simulation within education, training, and clinical environments.We advocate for healthcare systems and education institutions to commit themselves to the goal of high-quality healthcare and improved patient outcomes. This commitment should encompass the promotion and resource support of simulation-based learning opportunities for individuals and interprofessional teams throughout all stages and levels of a caregiver's career, in alignment with best practice standards.We call upon simulation practitioners to champion healthcare simulation as an indispensable learning tool, adhere to best practice standards, maintain a commitment to lifelong learning, and persist in their fervent advocacy for patient safety.This statement, the result of an international collaborative effort, aims to establish a consensus on the key priorities for the broad adoption of exemplary simulation practice that benefits patients and healthcare workforces globally.